1979
DOI: 10.1126/science.203.4383.892
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Io by Tidal Dissipation

Abstract: The dissipation of tidal energy in Jupiter's satellite Io is likely to have melted a major fraction of the mass. Consequences of a largely molten interior may be evident in pictures of Io's surface returned by Voyager I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
304
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(327 citation statements)
references
References 11 publications
4
304
0
1
Order By: Relevance
“…Being embedded in the Jovian magnetosphere, they are exposed to the complex flux of low-(plasma) and high-energy electron and ion bombardment (Dalton et al 2010). Io's surface is in fact dominated by sulfur dioxide, which is expelled from the very intense volcanic activity triggered by tidal effects (Peale et al 1979). Although it is thought that Io has lost nearly all of its hydrogen (Zolotov & Fegley 1999), the detection of hydrogen pickup ions by Galileo's plasma analyser (Frank & Paterson 1999) in the space surrounding the satellite raised the question regarding its origin.…”
Section: Solar System Objectsmentioning
confidence: 99%
“…Being embedded in the Jovian magnetosphere, they are exposed to the complex flux of low-(plasma) and high-energy electron and ion bombardment (Dalton et al 2010). Io's surface is in fact dominated by sulfur dioxide, which is expelled from the very intense volcanic activity triggered by tidal effects (Peale et al 1979). Although it is thought that Io has lost nearly all of its hydrogen (Zolotov & Fegley 1999), the detection of hydrogen pickup ions by Galileo's plasma analyser (Frank & Paterson 1999) in the space surrounding the satellite raised the question regarding its origin.…”
Section: Solar System Objectsmentioning
confidence: 99%
“…Mayor et al showed that this planet's eccentricity occasionally reaches values of 0.1. Applying common models of tidal heating (e.g., Peale et al 1979;Jackson et al 2008aJackson et al , 2008bBarnes et al 2009), and assuming the planet to be terrestrial-like, GJ 581 e could have 2 orders of magnitude more tidal heating than Jupiter's volcanic satellite Io! Although this planet is not in the IHZ, similar heating rates on planets in the IHZ are unlikely to develop life (Jackson et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The value for Mercury is Q Mercury < 190, and for Venus it is Q Venus < 17 (Goldreich and Soter, 1966). Observations of Io imply Q Io < 100 (Peale et al, 1979;Segatz et al, 1988), while the Moon lies at Q Moon = 26.5 -1 (Dickey et al, 1994). These measurements indicate a similar order of magnitude for the tidal dissipation function of all desiccated bodies in the Solar System.…”
Section: E4 Tidal Response In Celestial Bodiesmentioning
confidence: 74%
“…Tidal heating is responsible for the volcanism on Io (Strom et al, 1979;Laver et al, 2007), which was predicted by Peale et al (1979) with the use of tidal theory. Io is a small body orbiting Jupiter with an eccentricity of 0.0041 that is maintained by the gravitational perturbations of its fellow Galilean moons and shows global volcanism that resurfaces the planet on a timescale of 100 to 10 5 years ( Johnson et al, 1979;Blaney et al, 1995;McEwen et al, 2004).…”
Section: Introductionmentioning
confidence: 98%